دراسة واقع المواصلات ومنعكساته على التنمية في ريف محافظة اللاذقية (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى دراسة واقع المواصلات في ريف محافظة اللاذقية و انعكاس هذا الواقع على التنمية الريفية . حيث قمنا بدراسة انعكاس واقع المواصلات في الريف على كل من : التنمية البشرية للمواطن في الريف . المستوى الاقتصادي للأسرة الريفية . الهجرة الريفية . - استخدم البحث المنهج الوصفي التحليلي ، و كانت أداة البحث استبانة مؤلفة من محورين ، المحور الأول : تضمن معلومات عامة عن الأسرة الريفية . و المحور الثاني : تضمن واقع خدمات النقل في الريف . و قد وزعت هذه الاستبانة على عينة الدراسة البحثية التي بلغت 500 أسرة . و خلص البحث إلى مجموعة من النتائج أهمها ما يلي : - بينت الاختبارات الاحصائية الانعكاس السلبي لاستخدام وسائل النقل في الريف على التنمية البشرية للمواطن الريفي - وجود علاقة عكسية و متوسطة بين الانفاق على وسائل النقل و المستوى المعيشي للأسرة الريفية . - يشكل واقع المواصلات في الريف دافعاً قوياً للهجرة الريفية . This research aims To study the reality of transportation in the countryside of Lattakia , and the reflection of this reality on the rural development . where we studied the impact of the reality of transportation in the countryside on both : - Human development of rural citizen . - Economic level of the rural household. - Rural Migration . And the use of systematic, and descriptive research . the research tool was a questionnaire authoress of tow element . the first exist contains general information about the rural family . and the second exist deals with the reality of rural transport services . This questionnaire was distributed to a search sample which included of 500 family . the research resulted to a number of results : - Statistical tests showed a negative reflection of the use of rural transport on the human development of rural citizens . - there is an inverse and moderate relationship between expenditure on transportation and living standards of rural households . - the reality of rural transport is a strong case of rural migration .